Protection of Centrifugal Compressor System - Khalafullah A. Husayn (Journal of Electronic Design Engineering, 2021)
Surge and Choke phenomenon are the two unstable operating modes of a compression system. That surge mode occurs at mass flows below the so-called surge line, and the chock mode occurs at low pressure and high flow rate. These instability operation modes will reduce the compressor performance or even will be made damage to the compressor system. There are many studies to prevent instability phenomenon by establishing control system to the ability to do that, but sometimes surge or chock phenomenon occurs although of this big effort. So, for this reason, the paper focus on the protection system, introduced to detect and prevent surge and shock stall occurrence to reduce damages possibility and keep the production at minimum losses. This can be achieved by setting the mass flow rate, pressure ratio, and operating speed in a predefined area. Depending on the data sets including measurements from compression systems of Sirte Oil Company, Libya, and performance characteristics curves and polynomial regression technique to define the operation area. The developed surge protection system was implemented on the Matlab Simulink program and presented in a simple form.